The mechanisms of effect of a physiotherapist-delivered integrated psychological and exercise intervention for acute whiplash-associated disorders: secondary mediation analysis of a randomized controlled trial. (23rd September 2020) - Elphinston, Rachel A.; Sterling, Michele; Kenardy, Justin; Smeets, Rob; Armfield, Nigel R.
Abstract : Supplemental Digital Content is Available in the Text. Stress mediated the effect of a physiotherapist-delivered integrated intervention on multiple health outcomes and pain-related coping mediated the effect on pain self-efficacy only. Changes in depressive and posttraumatic stress symptoms were also mechanisms of effect. Abstract: Introduction: Integrated psychological and physical treatments can improve recovery for whiplash-associated disorders (WADs). Little is known about how these interventions work. Objective: To examine the mechanisms by which a physiotherapist-delivered integrated intervention for acute WAD improves health outcomes. Methods: Secondary analysis using structural equation modelling of a randomized controlled trial comparing integrated stress inoculation training and exercise to exercise alone for acute WAD. Outcomes were disability, pain self-efficacy, pain intensity, and health-related quality of life at 12 months. The intended intervention target and primary mediator, stress was tested in parallel with pain-related coping, an additional cognitive behavioral mediator that significantly improved at posttreatment (Model 1). Stress-related constructs that commonly co-occur with stress and pain were also tested as parallel mediators: depression and pain-related coping (Model 2); and posttraumatic stress and pain-related coping (Model 3). Results: Reductions in stress mediated the effect of the integrated intervention on disability (β = −0.12, confidence interval [CI] = −0.21 to −0.06), pain self-efficacy (β = 0.09, CI = 0.02–0.18), pain (β = −0.12, CI = −0.21 to −0.06), and health-related quality of life (β = 0.11, CI = 0.04–0.21). There was an additional path to pain self-efficacy through pain-related coping (β = 0.06, CI = 0.01–0.12). Similar patterns were found in Models 2 and 3. Conclusions: Improvements in stress and related constructs of depression and posttraumatic stress, and pain-related coping were causal mechanisms of effect in a physiotherapist-delivered integrated intervention. As integrated interventions are growing in popularity, it is important to further personalize interventions for improved benefit.